Chemical characterization (C, H, N, and S) of size fractionated particles from a highway tunnel Caracas ”“Venezuela - Fernández, Raiza; Martinez, Manuel; Galarraga, Federico (Ciencia)
Settled particles collected in El Paraiso highway tunnel, located at the western Caracas (Venezuela) have been fractionated in five sizes 35, 60, 120, 230 and 325 meshes (500, 250, 125, 60 y 45 Âµm) and analyzed for carbon, hydrogen, nitrogen and sulphur; in addition, organic and inorganic content of sulphur were determined. The aim of this work is to gain some insight into elemental composition and distribution of these elements in this kind of material. The results indicated the presence of different organic and inorganic species for both, carbon and sulphur elements. Inorganic sulphur is present mainly as sulphate; carbonate is the main chemical form for inorganic carbon. Carbon and sulphur elements were highly concentrated in the fine fraction (45 Âµm). Nitrogen might be mainly associated to the organic matter since it was no detected in aqueous phase by ionic chromatography. H/C ratio between 1.0-1.5 suggest that the hydrogen is strongly associated to the organic matter, specifically saturated and aromatic hydrocarbons. This result provides evidences of a common input for organic carbon and sulphur by fossil fuel combustion due to motor vehicle emissions.